Hubungan Status Pekerjaan Ibu dengan Berat Lahir Bayi di RSUP Dr. M. Djamil Padang - Yuliva Djauhar Ismail, Diah Rumekti (Fakultas Kedokteran Universitas Gadjah Mada, 2009)
Background: According to 2002-2003 Indonesia Demography Health Survey (IDHS), the percentage distribution of women based on job status in the past 12 months in West Sumatera showed that 57,5% of woman was working, 2,4% of woman was not working and 40,1% of the women did not work at all. From the data, it is shown that the percentage of woman who working was bigger than woman who was not working. Based on various researches, a job that will be done by a woman especially while pregnant, had influence toward the weight of the infant who will be delivered.Objective: This research was aimed to find out the relationship of job status and job type of mother with infant’s birth weight in RSUP Dr. M. Djamil Padang.Method: This was an observational research that used Prospective Cohort design. The data was collected in antenatal polyclinic of RSUP Dr.M. Djamil Padang. The population was all pregnant women who came to check their pregnancies to antenatal polyclinic and they were clustered based on job status and job type. Every pregnant woman was observed and their pregnancy development that was started in the week 32 of pregnancy until delivery was continually monitored. The sample was taken with non probability sampling and consecutive sampling. The independent variables were job status and job type and the dependent variable was infant’s birth weight. The confounding variable were education, social economy status, women’s age, parity, gestation age, women’s height, weight gain, nutrition intake, children sex and mother’s disease during pregnancy.Result: The dif ference of birth weight in a mother works with heavy physical activity was 196.44 gram (p=0.000) which was lower than mother who did not work with heavy physical activity, and the difference of infant’s birth weight in the group of mother who were ill during pregnancy with those who were not ill in their pregnancy period was 243.92 gram (p=0.001). Male infant who was born had difference on the average of birth weight that was 97.24 gram (p=0.015) which was heavier than female infant. The increasing gestation age every one week will increase infant’s birth weight 45.34 gram (p=0.021) and increasing of mother’s weight will increase infant’s birth weight with 47.12 gram (p=0.000). The increasing nutrition intake every one kilocalories will increase infant’s birth weight 0.56 gram (p=0.000). R2 was 0.2729 which mean that model 2 as the result of double linear regression analysis could explain the relationship and predicted infant’s birth weight with 27.29%.Conclusion: There was a relationship between mother’s job status (working or not working) and mother’s job type (heavy physical activity and low physical activity) with infant’s birth weight, in which infant’s birth weight in working mother with heavy physical activity was lower than infant with mothers who did not work with heavy physical activity.Keywords: job status, job type and infant’s birth weight